Pengaruh Job Demand dan Job Resources terhadap Work Engagement pada Karyawan PT. Sukseskan Pangan Indonesia - Arga Seno Prasetyo Pribadi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of Job Demand and Job Resources on Work Engagement of employees of PT. Sukseskan Pangan Indonesia. The research approach used is quantitative with a survey method through a questionnaire as the main instrument. The research sample was determined using the Slovin formula with a 5% error tolerance level, resulting in 45 respondents from a population of 50 employees. The data obtained were analyzed using validity, reliability, and multiple linear regression tests. The results of the study indicate that Job Demand does not have a significant effect on Work Engagement, while Job Resources have a positive and significant effect on Work Engagement. Simultaneously, Job Demand and Job Resources together have a significant effect on Work Engagement. This indicates that the support of work resources, such as autonomy, technology, and a conducive work environment, can increase employee engagement in work. In conclusion, this study emphasizes the importance of increasing Job Resources in supporting employee Work Engagement. PT. Sukseskan Pangan Indonesia is advised to strengthen technology support to improve work effectiveness, especially for employees from the millennial generation. Keywords: Job Demand, Job Resources, Work Engagement